Meteorological rhythms of respiratory and circulatory diseases revealed by Harmonic Analysis. Issue 5 (May 2020) - Ma, Pan; Wang, Shigong; Zhou, Ji; Li, Tanshi; Fan, Xingang; Fan, Jin; Wang, Siyi
Abstract: The intricately fluctuating onset of respiratory and circulatory diseases displays rhythms of multi-scaled meteorological conditions due to their sensitivity to weather changes. The intrinsic meteorological rhythms of these diseases are revealed in this bio-meteorological study via Fourier decomposition and harmonic analysis. Daily emergency room (ER) visit data for respiratory and circulatory diseases from three comprehensive hospitals in Haidian district of Beijing, China were used in the analysis. Meteorological data included three temperature metrics, relative humidity, sunshine duration, daily mean air pressure, and wind speed. The Fourier decomposition and harmonic analysis on ER visits and meteorological variables involve frequency, period, and power of all harmonics. The results indicated that: i) for respiratory morbidity, a strong climatic annual rhythm responding to annual temperature change was firstly revealed; its ratio of spectral density was 16–33%. Moreover, significant correlations existed between the high-frequency fluctuations (<30 d) of morbidity and short-term harmonics of humidity and solar duration. High-frequency harmonics of temperature and pressure showed no statistically significant effect. ii) With regard to all types of circulatory morbidity, their annual periodicity was weaker than that of respiratory diseases, whose harmonic energy took a ratio less than 8%. Besides, the power of all high-frequency harmonics of circulatory morbidity accounted for up to 70–90% in the original sequences, and their relationship to many short-term meteorological factors were significant, including the mean and maximum temperatures, wind speed, and solar duration. iii) The weekly rhythm appeared in respiratory ER visits with 15% of harmonic variance but not prominent in circulatory morbidity. In summary, by decomposing the sequence of respiratory and circulatory diseases as well as recognizing their meteorological rhythms, different responses to meteorological conditions on various time scales were identified. Abstract : Harmonic spectrum; Fourier decomposition; Chronic disease; Climatic cycle; Short-term weather; Meteorology; Climatology; Environmental health; Epidemiology; Circulatory system; Respiratory system, Environmental science.